2021
DOI: 10.1016/j.diagmicrobio.2020.115197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 fully automated tests detecting antibodies against nucleocapsid N and spike S1/S2 proteins in COVID-19

Abstract: Automated assays for detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies in coronavirus disease 2019 (COVID-19) diagnostics have recently come available. We compared the performance of the Elecsys® Anti–SARS-CoV-2 and LIAISON® SARS-CoV-2 S1/S2 IgG tests. The seroconversion panel comprised of 120 samples from 13 hospitalized COVID-19 patients. For the sensitivity and specificity testing, samples from COVID-19 outpatients >15 days after positive nucleic acid amplification test (NAAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…A high proportion of seropositives also demonstrated both S and RBD IgG responses, and there was good correlation in serostatus across the 3 antigens. Whilst the value of N protein only based platforms has generated some debate in view of the weaker correlation with viral neutralising activity compared with S and RBD binding assays (19), our data supports other reports showing that N protein based assays are most sensitive for detection of serum responses(20, 21). Within the seropositive cohort, we found no relationship between symptom score and the spectrum of binding activity to the 3 antigens tested (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…A high proportion of seropositives also demonstrated both S and RBD IgG responses, and there was good correlation in serostatus across the 3 antigens. Whilst the value of N protein only based platforms has generated some debate in view of the weaker correlation with viral neutralising activity compared with S and RBD binding assays (19), our data supports other reports showing that N protein based assays are most sensitive for detection of serum responses(20, 21). Within the seropositive cohort, we found no relationship between symptom score and the spectrum of binding activity to the 3 antigens tested (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…In the short-term range of 2 weeks after infection, there are no differences between sensitivity of assays targeting antibodies against the nucleocapsid or the spike protein [ 25 ]. In recent comparisons of nucleocapsid- and spike-protein-based assays, no unambiguous superiority of one approach or the other could be identified [ 26 , 27 , 28 , 29 ]. In early infection states, sensitivity of anti-nucleocapsid antibodies can even be higher than that of anti-spike protein antibodies [ 24 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low sensitivity early in infection could be a result of an assay detecting only IgG antibodies, but both the Ortho and Abbott IgG-specific assays had higher 0-14 day sensitivities which were similar to the total antibody assays. Other assay validation studies have reported similarly high sensitivities for samples collected after at least 14 days 6 , 7 , 8 , 9 , 10 . In the outbreak field study, where all samples were collected >14 days and within 2 months post-onset, >95% sensitivity was observed for all assays.…”
Section: Discussionmentioning
confidence: 63%